Features of brewing technology from unconventional raw materials - Романова, З. М.; Косоголова, Л. О. (Problems of Environmental Biotechnology, 2013)
The composition and properties of polymalt extracts as a base for non-alcoholic beverages were investigated. The optical ratios of polymalt extract, raspberry water extract and needed amount of glucose-fructose syrup were selected for obtaining of balanced beverage on components composition with harmonious taste.